Fabrication, Testing and Characterization of MEMS Gyroscope - Almikhlafi, Ridha (University of Waterloo, 2017)
This thesis presents the design, fabrication and characterization of two Micro-Electro-Mechanical Systems (MEMS) vibratory gyroscopes fabricated using the Silicon-On-Insulator-Multi-User-MEMS Process (SOIMUMPs) and Polysilicon Multi-User-MEMS-Process (Poly-MUMPs). Firstly, relevant literature and background on static and dynamic analysis of MEMS gyroscopes are described. Secondly, the gyroscope analytical model is presented and numerically solved using Mathematica software. The lumped mass model was used to analytically design the gyroscope and predict their performance. Finite element analysis was carried out on the gyroscopes to verify the proposed designs. Thirdly, gyroscope fabrication using MEMSCAP's SOIMUMPs and PolyMUMPs processes is described. For the former, post-processing was carried out at the Quantum Nanofab Center (QNC) on a die-level in order to create the vibratory structural elements (cantilever beam). Following this, the PolyMUMPs gyroscopes are characterized optically by measuring their resonance frequencies and quality factor using a Laser Doppler Vibrometer (LDV). The drive resonance frequency was measured at 40 kHz and the quality factor as Q = 1. For the sense mode, the resonance frequency was measured at 55 kHz and the unity quality factor as Q = 1. The characterization results show large drive direction motions of 100 um/s in response to a voltage pulse of 10 V. The drive pull-in voltage was measured at 19 V. Finally, the ratio of the measured drive to sense mode velocities in response to a voltage pulse of 10 V was calculated at 1.375.
Keywords: MEMS Gyroscope; In-Plane Mode; Out-of-Plane Mode; Coriolis Force; Electrostatic Actuation; PolyMUMPs; SOIMUMPs; Fabrication